2022
DOI: 10.3390/ph15070852
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning Linagliptin for the Mitigation of Cadmium-Induced Testicular Dysfunction in Rats: Targeting HMGB1/TLR4/NLRP3 Axis and Autophagy

Abstract: Cadmium, a ubiquitous environmental toxicant, disrupts testicular function and fertility. The dipeptidyl peptidase-4 inhibitor linagliptin has shown pronounced anti-inflammatory and anti-apoptotic features; however, its effects against cadmium-evoked testicular impairment have not been examined. Herein, the present study investigated targeting inflammation, apoptosis, and autophagy by linagliptin for potential modulation of cadmium-induced testicular dysfunction in rats. After 60 days of cadmium chloride admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…They ascribed stimulation of autophagic mechanisms to the documented activation of the AMPK/mTOR pathway. 33,61 Regarding the role of autophagy in carcinogenesis, interestingly, autophagy as previously stated, plays two contradicting tumor-suppressive or tumor-promoting roles depending mainly on the stage of neoplasm, tumor genetics, immune response, and nutritional factors. 62,63 During the early stages of oncogenesis, autophagy acts as a tumor suppressor via inhibiting aberrant cellular proliferation, invasion, and metastasis that could be attributed to the crucial role of autophagy in maintaining genomic stability, preventing intracellular aggregation of oncoproteins and elimination of defective organelles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They ascribed stimulation of autophagic mechanisms to the documented activation of the AMPK/mTOR pathway. 33,61 Regarding the role of autophagy in carcinogenesis, interestingly, autophagy as previously stated, plays two contradicting tumor-suppressive or tumor-promoting roles depending mainly on the stage of neoplasm, tumor genetics, immune response, and nutritional factors. 62,63 During the early stages of oncogenesis, autophagy acts as a tumor suppressor via inhibiting aberrant cellular proliferation, invasion, and metastasis that could be attributed to the crucial role of autophagy in maintaining genomic stability, preventing intracellular aggregation of oncoproteins and elimination of defective organelles.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reported Beclin‐1 upregulation and diminished p62 accumulation in the current work coincide well with previous studies that demonstrated induction of autophagy following LNGTN treatment in in vivo animal models of neurodegeneration and testicular damage. They ascribed stimulation of autophagic mechanisms to the documented activation of the AMPK/mTOR pathway 33,61 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LNG is used to treat other conditions as well, including polycystic ovary syndrome [2] and more recently, testicular dysfunction brought on by cadmium [3]. Negative effects of LNG include irritation of the nose and throat, while dangerous effects include pancreatitis, angioedema, and arthritic pain [3].…”
Section: Introductionmentioning
confidence: 99%